2019
DOI: 10.1128/jvi.01309-19
|View full text |Cite
|
Sign up to set email alerts
|

Absence of Signal Peptide Peptidase, an Essential Herpes Simplex Virus 1 Glycoprotein K Binding Partner, Reduces Virus InfectivityIn Vivo

Abstract: We previously reported that herpes simplex virus (HSV) glycoprotein K (gK) binds to signal peptide peptidase (SPP), also known as minor histocompatibility antigen H13. Binding of gK to SPP is required for HSV-1 infectivity in vitro. SPP is a member of the γ-secretase family, and mice lacking SPP are embryonic lethal. To determine how SPP affects HSV-1 infectivity in vivo, the SPP gene was deleted using a tamoxifen-inducible Cre recombinase driven by the ubiquitously expressed ROSA26 promoter. SPP mRNA was redu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
43
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(56 citation statements)
references
References 69 publications
9
43
4
Order By: Relevance
“…gK is mainly involved in viral entry into corneal epithelial cells, membrane fusion, the intracellular spread of virions, and virion egress (86). Many studies support the viewpoint that gK plays important roles in viral replication and corneal scarring (6,87). Lack of gK can reduce virus transmission to the corneal epithelium and TG, which prevents the establishment of latency and thus inhibits viral replication and reduces the development of corneal nerve damage (88,89).…”
Section: The Role Of Glycoproteins In Hskmentioning
confidence: 99%
See 1 more Smart Citation
“…gK is mainly involved in viral entry into corneal epithelial cells, membrane fusion, the intracellular spread of virions, and virion egress (86). Many studies support the viewpoint that gK plays important roles in viral replication and corneal scarring (6,87). Lack of gK can reduce virus transmission to the corneal epithelium and TG, which prevents the establishment of latency and thus inhibits viral replication and reduces the development of corneal nerve damage (88,89).…”
Section: The Role Of Glycoproteins In Hskmentioning
confidence: 99%
“…They found that overexpression of gK increased the severity of corneal scarring by altering how the virus bound to the receptor by modulating the expression of HSV-1 receptors, such as 3-OS-HS, HVEM, and nectin-1 or nectin-2 (91). One hypothesis is that binding of gK to signal peptide peptidase (SPP) exacerbates corneal scarring and leads to blindness (87,92). The pathogenicity of this combination is mainly manifested as increased viral replication and the establishment of latency, as well as enhanced numbers of viral transcripts in the cornea and TG (87).…”
Section: The Role Of Glycoproteins In Hskmentioning
confidence: 99%
“…This compound also reduced HSV-1 replication in vivo when topically applied before and during ocular infection of mice. Recently, the role of SPP for HSV-1 infectivity in vivo was further confirmed in a genetic model [108]. Since constitutive SPP knockout mice are lethal [102], a floxed SPP locus in combination with a tamoxifen-inducible Cre recombinase was employed [108].…”
Section: Viral Infectionsmentioning
confidence: 99%
“…Recently, the role of SPP for HSV-1 infectivity in vivo was further confirmed in a genetic model [108]. Since constitutive SPP knockout mice are lethal [102], a floxed SPP locus in combination with a tamoxifen-inducible Cre recombinase was employed [108]. Mice with induced SPP deletion exhibited significantly less HSV-1 replication in their eyes.…”
Section: Viral Infectionsmentioning
confidence: 99%
See 1 more Smart Citation